The Legal Status of the Donetsk and Luhansk “Peoples’ Republics” - Короткий, Тимур Робертович; Korotkyi, Tymur R.; Короткий, Т. Р.; Хендель, Наталія Володимирівна; Хендель, Н. В.; Хендель, Наталия Владимировна; Khendel, Nataliia V. (ASSER PRESS, 2018)
In this chapter, issues of legitimacy surrounding the creation/proclamation of the “Donetsk People’s Republic” (DPR) and the “Luhansk People’s Republic” (LPR) are considered. The international legal aspects of the recognition of the DPR and the LPR are also analysed. In addition, the position adopted by the Russian Federation and the international community towards these so-called people’s republics is revealed.

У цьому розділі розглядаються питання легітимності створення/проголошення «Донецької народної республіки» (ДНР) та «Луганської народної республіки» (ЛНР). Також аналізуються міжнародно-правові аспекти визнання ДНР та ЛНР. Крім того, розкривається позиція Російської Федерації та міжнародного співтовариства щодо цих так званих народних республік.
Korotkyi T. The Legal Status of the Donetsk and Luhansk “Peoples’ Republics” / T. Korotkyi, N. Hendel // The Use of Force against Ukraine and International Law. - ASSER PRESS, 2018. – P. 145-170.
Keywords: legitimacy of the creation/proclamation; unrecognized state; separatist formation; recognition; territorial integrity of Ukraine; the “Donetsk People’s Republic”; the “Luhansk People’s Republic”; легітимність створення/проголошення; невизнана держава; сепаратистське формування; визнання; територіальна цілісність України; «Донецька народна республіка»; «Луганська Народна Республіка»; Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law